ant(6)-I Genes Encoding Aminoglycoside O-Nucleotidyltransferases Are Widely Spread Among Streptomycin Resistant Strains of Campylobacter jejuni and Campylobacter coli - Hormeño, Lorena; Ugarte-Ruiz, María; Palomo, Gonzalo; Borge, Carmen; Florez-Cuadrado, Diego; Vadillo, Santiago; Píriz, Segundo; Domínguez, Lucas; Campos, Maria J.; Quesada, Alberto (Frontiers in Microbiology, 2018)
Thermotolerant Campylobacter species C. jeuni and C. coli are actually recognized as the major bacterial agent responsible for food-transmitted gastroenteritis. The most effective antimicrobials against Campylobacter are macrolides and some, but not all aminoglycosides. Among these, susceptibility to streptomycin is reduced by mutations in the ribosomal RPSL protein or by expression of ANT(6)-I aminoglycoside O-nucleotidyltransferases. The presence of streptomycin resistance genes was evaluated among streptomycin-resistant Campylobacter isolated from humans and animals by using PCR with degenerated primers devised to distinguish ant(6)-Ia, ant(6)-Ib and other ant-like genes. Genes encoding ANT(6)-I enzymes were found in all possible combinations with a major fraction of the isolates carrying a previously described ant-like gene, distantly related and belonging to the new ant(6)-I sub-family ant(6)-Ie. Among Campylobacter isolates, ant(6)-Ie was uniquely found functional in C. coli, as shown by gene transfer and phenotype expression in Escherichia coli, unlike detected coding sequences in C. jejuni that were truncated by an internal frame shift associated to RPSL mutations in streptomycin resistant strains. The genetic relationships of C. coli isolates with ANT(6)-Ie revealed one cluster of strains presented in bovine and humans, suggesting a circulation pathway of Campylobacter strains by consuming contaminated calf meat by bacteria expressing this streptomycin resistance element.